JENIS-JENIS BURUNG (AVES) DI KAWASAN DANAU SIPOGAS KABUPATEN ROKAN HULU PROVINSI RIAU - Hasibuan, Minta Ito; Ade, Filza Yulina; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of this study was to determinethe species of birds in Sipogas lake. This study has been carried out in december 2014 to Januari 2015 with survey method andline transek. Birds which founded than identified by describing the species of the birds.Result showed 3 order, 8 family, 9 genera, 11 species and total 53 individual of birds was found in this study. The species were Aplonis pananyensis, Choloropsis cynopogon, Delichon dasypus, Geopelia striata, Loriculus galgulus, Passer montanus, Prinia inornata, Pycnonotus aurigaster, P. brunneus, P. simplex dan Streptopelia chinensis.